PENGARUH MEDIA PEMBELAJARAN BERBASIS POWTOON TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Hutabarat, Agape; Siregar, Arifin; Simanjuntak, Sorta; Simanihuruk, Lidia; Prawijaya, Septian (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to determine the effect of powtoon-based learning media on the mathematics learning outcomes of class V students at public elementary school 177076 Lumban Nabolon T.A 2023/2024. This type of research is Pre-Experimental Design in the form of One Group Pretest-Posttest Design. In this research, the research subjects were 32 students in class V of SD Negeri 177076 Lumban Nabolon. During the research, the researcher gave a pre-test to the subjects after which the subjects were given treatment using powtoon-based learning media. Research data was obtained from test results and analyzed using immersion analysis tests and hypothesis testing using the t-test. The average pre-test result was 53.28 and the average post-test result was 75.62. These results indicate that there is an influence of learning media on the mathematics learning outcomes of class V students at SD Negeri 177076 Lumban Nabolon. The results of the pre-test post-test t-test obtained a p value of 0.001 < 0.05. These results indicate that the learning media applied has a significant influence on improving student learning outcomes, where student learning scores using Powtoon-based learning media are higher.